2017
DOI: 10.1177/1753193417691653
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of grafting intrasynovial tendons of the toes to the hands in 10 patients: a preliminary report

Abstract: Ten patients had intrasynovial tendon grafting harvested from the toes for secondary flexor tendon reconstruction in nine fingers and one thumb in our institutes from 2009 to 2014. These patients were followed for a mean of 15 (range: 8-36) months. The ranges of total active motion of the proximal and distal interphalangeal joints of these nine fingers were 143° (range: 108-175°) and of the metacarpophalangeal and interphalangeal joints of one thumb were 110°. In conclusion, this technique is feasible and give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…In recent years, early active mobilization has been recommended after tendon grafting. 14 , 15 , 16 , 17 , 18 Our results are consistent with prior series with rupture rates of 0% to 27%, recovery rates of 59% to 84%, and AROM at the final visit of 96° to 136° ( Table 4 ). Theoretically, early active mobilization after flexor tendon grafts could decrease adhesion formation and improve patient outcomes compared with immobilization or the Kleinert technique.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In recent years, early active mobilization has been recommended after tendon grafting. 14 , 15 , 16 , 17 , 18 Our results are consistent with prior series with rupture rates of 0% to 27%, recovery rates of 59% to 84%, and AROM at the final visit of 96° to 136° ( Table 4 ). Theoretically, early active mobilization after flexor tendon grafts could decrease adhesion formation and improve patient outcomes compared with immobilization or the Kleinert technique.…”
Section: Discussionsupporting
confidence: 91%
“…26e28 Gelberman et al 29 suggested that the unique angiogenic response of intrasynovial flexor tendon grafts may allow healing with only minimal ingrowth of vascular adhesions. Recently, free-tendon grafting using intrasynovial donor tendons was performed in an effort to reduce adhesion formation 16,17 ; however, the clinical results seem to be similar to those obtained after extrasynovial tendon grafting (Table 4). Compared with intrasynovial tendons, the weak point when using extrasynovial tendons as free grafts is likely to be the grip of the sutures at the distal tendonebone junctions.…”
Section: Discussionmentioning
confidence: 96%
“…However, it should be noted that the majority of cases in the case series reported here did not have any pulley reconstruction, and the gliding sheath was intact, which is different from those previous series of two-stage tendon reconstruction. The case series presented by Ohi et al (2017) had a similar functional return to the patients in this report. We believe that our technique results in functional return similar to a one-stage tendon graft, but we cannot state that this will be an alternative to two-stage tendon reconstruction.…”
Section: Discussionsupporting
confidence: 71%
“…58,59 No direct comparison has demonstrated the superiority of intrasynovial to extrasynovial grafts. 60,61 The most commonly used donor grafts are the extrasynovial palmaris longus or plantaris tendons.…”
Section: Source Of Donor Tendonmentioning
confidence: 99%